DAMPAK THIRD WAVE COFFEE CULTURE TERHADAP FENOMENA PENIKMAT KOPI DI KOTA PEKANBARU - Muhammad Thoriq Alfarras; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research describes and analyzes about the impact of third wave coffee culture towards the coffee connoisseur in Pekanbaru. Third wave coffee culture is a phenomenon that makes the coffee getting the plus value. This research uses the globalization concept by using four indicators namely describing about the impact of third wave coffee culture in Pekanbaru as one of province in Indonesian that has potential because of coffee producing in Indonesian. The method that is used in this research is descriptive by data collecting through the library case. In this research, the researcher uses the constructivism theory and globalization concept. The writer uses the theory and the concept in order to ease the research in analyzing how the impact of third wave coffee culture towards the coffee connoisseur in Pekanbaru. The result of this research shows that the coffee shop of third wave often pays attention to the quality of coffee seed, manual brewing technique, and also the amount of ceoffee served. That attention is reached by the knowledge bargaining between the barista and the consument. But, for getting the impression as coffee shop customer, the coffee shop customer doesn’t need to be active to communicate with the barista. But, they just come in the shop of third wave. Therefore, the customer will get the impression and the meaning that they are the customer coffee of third wave that care enough. Keywords: Third Wave Coffee Culture, Globalization, Coffee Shop in Pekanbaru.